2010
DOI: 10.1186/1475-2859-9-22
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of Skp and FkpA chaperones improves cell viability and alters the global expression of stress response genes during scFvD1.3 production

Abstract: BackgroundThe overexpression of scFv antibody fragments in the periplasmic space of Escherichia coli frequently results in extensive protein misfolding and loss of cell viability. Although protein folding factors such as Skp and FkpA are often exploited to restore the solubility and functionality of recombinant protein products, their exact impact on cellular metabolism during periplasmic antibody fragment expression is not clearly understood. In this study, we expressed the scFvD1.3 antibody fragment in E. co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 71 publications
2
26
0
Order By: Relevance
“…FkpA has been reported to improve protein solubility as well as catalyze prolyl isomerization for several model proteins. 14,[19][20][21] In addition, FkpA localized to the cytoplasm has also been shown to enhance secretion of both Fabs and scFv into the E. coli periplasm, possibly by helping each stay soluble long enough for export from the cytoplasm. 22 However, FkpA alone is insufficient to support IgG assembly (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…FkpA has been reported to improve protein solubility as well as catalyze prolyl isomerization for several model proteins. 14,[19][20][21] In addition, FkpA localized to the cytoplasm has also been shown to enhance secretion of both Fabs and scFv into the E. coli periplasm, possibly by helping each stay soluble long enough for export from the cytoplasm. 22 However, FkpA alone is insufficient to support IgG assembly (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that the solubility and affinity of scFv was improved by co-expression of molecular chaperones such as Skp, Dsbc, and FkpA (Ow et al, 2010; Sonoda et al, 2011). In some cases, co-expression of molecular chaperone not only improves the soluble expression but also increases the cell viability (Ow et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…FkpA has long been known to act as a chaperone for nonnative or mutant E. coli proteins (29)(30)(31), but until recently, its physiological role was largely unclear. It has been shown that FkpA is necessary for colicin M toxicity in vivo (32,33) and that its PPIase activity is required for this function (34).…”
mentioning
confidence: 99%